Hubungan Heart Rate Variability dengan Global Longitudinal Strain pada Pasien Diabetes Melitus Tipe 2 di Puskesmas Jakarta - Hadi, Dwi Rendra; Rusdi, Lusiani; Tarigan, Tri Juli Edi; Mansjoer, Arif (Jurnal Penyakit Dalam Indonesia, 2025)
Introduction. Diabetes mellitus (DM) remains a major global health issue due to its direct consequences and complications, particularly cardiovascular complications. These complications are influenced by autonomic neuropathy, which can be assessed by Heart Rate Variability (HRV). Autonomic dysfunction is thought to impair heart function, which can potentially be predicted early by observing Global Longitudinal Strain (GLS). The relationship between HRV and GLS has not been extensively studied. Therefore, this study aimed to identify the relationship between HRV and GLS. Methods. A cross-sectional study with a population of adult type 2 DM patients residing in Jakarta in December 2020. HRV parameters included RR interval, Standard Deviation of NN Intervals (SDNN), Root Mean Square of Successive Difference (RMSSD), Low Frequency (LF), High Frequency (HF), and LF/HF ratio. Global longitudinal strain was analyzed using echocardiography. Results. Analysis was conducted on 167 samples. The mean value of GLS was -20.30 (SD 1.57). There were no correlation between RR interval (r = -0.07, p = 0.377), SDNN (r = -0.10, p = 0.189), RMSSD (r = -0.12, p = 0.098), LF (r = -0.003, p = 0.968), HF (r = -0.09, p = 0.21), and LF/HF ratio (r = -0.10, p = 0.189) with GLS. No association was found between hypertension, history of smoking, dyslipidemia, duration of diabetes, and HbA1C with GLS. Conclusion. There is no correlation between heart rate variability and global longitudinal strain in type 2 DM patients.